Aplikasi Sistem Pakar Diagnosis Penyakit HIV/AIDS Menggunakan Metode Forward Chaining Berbasis Web - Yoga Handoko Agustin; Wiyoga Baswardono; Falah Insan Pratama (Institut Teknologi Garut, 2022)
With the growth of technology, some jobs have used computers to help diagnose a disease, especially HIV/AIDS. Expert systems are artificial intelligence that is growing rapidly in the world of technology. Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) are different but related diseases. A different but related disease, while HIV is a virus that causes AIDS. This virus attacks the human immune system, so it can cause other infections to enter the human body. Often a person experiences symptoms of illness that are considered normal, such as fever to chills, vomiting, joint pain, muscle pain, headaches, and many more. These symptoms are characteristics of HIV symptoms, and to find out the disease one is suffering from doctor, a patient needs to go to a hospital or specialist clinic with a series of procedures to be able to consult a doctor, so that in this case it takes up a lot of the patient's time and is expensive to consult a doctor. The purpose of this research is to make an application for diagnosing HIV/AIDS to help people who have HIV/AIDS. Forward chaining inference method with Rational Unified Process (RUP) development methodology with Inception, Elaboration, Construction, and Transition stages. The result is an expert system for diagnosing HIV/AIDS using a web-based forward chaining method.